RESEÑA de : Prieto, E. ; Martínez, A. ; Muñoz, M. C. (coords.).Temas y perspectivas de la educación : la educación social ¿realidad o mito?. Salamanca : Hergar, 2013. - Rebolledo, Teresa; Rodríguez, Mª del Rocío; Muñoz, Julia (Revista Española de Educación Comparada, 2014)
-